2005
DOI: 10.1029/2004jc002731
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in total organic carbon in the northeast Atlantic in 2000–2001

Abstract: [1] Total organic carbon (TOC) was measured in the midlatitudes of the northeast Atlantic in 2000-2001 during the Programme Océan Multidisciplinaire Méso Echelle (POMME). In spring, mixed layer depth (MLD) was positively correlated with the north latitude, while the surface TOC and chlorophyll-a (Chl a) were negatively correlated with it. It indicates the northward propagation of TOC accumulation along the onset of spring bloom, which was triggered by shoaling of MLD from the south. Surface TOC was highest in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 32 publications
(68 reference statements)
1
54
0
1
Order By: Relevance
“…SSA hygroscopicity was reduced by 42% to κ = 0.81 (+0.33, À0.40) (Figure 2, period Z1) in association with the initial addition of bacteria culture, ZoBell media, and unfiltered seawater (A1) at t = 0.6 days. The TOC concentration in the seawater after this initial addition averaged 89 μM, approximately 20 μM higher than the unaltered seawater control, which is slightly higher than typical springtime regional averages [Sohrin and Sempere, 2005], but is well below values observed at the ocean surface in regions of high biological activity [Engel et al, 2012]. This initial suppression of aerosol hygroscopicity is attributed primarily to the influence of just the ZoBell media on the OM aero content.…”
Section: Impact Of Bacteria On Sea Spray Aerosolmentioning
confidence: 85%
See 1 more Smart Citation
“…SSA hygroscopicity was reduced by 42% to κ = 0.81 (+0.33, À0.40) (Figure 2, period Z1) in association with the initial addition of bacteria culture, ZoBell media, and unfiltered seawater (A1) at t = 0.6 days. The TOC concentration in the seawater after this initial addition averaged 89 μM, approximately 20 μM higher than the unaltered seawater control, which is slightly higher than typical springtime regional averages [Sohrin and Sempere, 2005], but is well below values observed at the ocean surface in regions of high biological activity [Engel et al, 2012]. This initial suppression of aerosol hygroscopicity is attributed primarily to the influence of just the ZoBell media on the OM aero content.…”
Section: Impact Of Bacteria On Sea Spray Aerosolmentioning
confidence: 85%
“…STXM-NEXAFS measurements of a collection of individual, internally mixed salt/organic particles also indicate an increase in the organic volume fraction of approximately 5% ( Figure S5). To date, this represents the largest observed change in CCN activity for ocean-relevant TOC (50-120 μM) [Sohrin and Sempere, 2005;Engel et al, 2012] and heterotrophic bacteria concentrations (approximately 5 × 10 5 -5 × 10 7 cells/mL) [Cho and Azam, 1990;Li, 1998]. Teeling et al [2012] recently observed heterotrophic bacteria concentrations of~3.6 × 10 6 cells mL À1 in the North Sea following periods of high photosynthetic biological activity (high chl a), which acted as the carbon source for the observed surge in bacterial growth in that locale.…”
Section: Impact Of Bacteria On Sea Spray Aerosolmentioning
confidence: 99%
“…Dissolved organic carbon (DOC) was measured using the high-temperature combustion method and either a TOC-V or TOC-5000 analyzer (Shimadzu) (Benner and Strom, 1993;Sohrin and Sempéré, 2005). Filtered water samples were stored frozen until analysis in laboratory.…”
Section: Doc Determinationmentioning
confidence: 99%
“…Analytical errors based on duplicate analysis were approximately 5 %. DOC concentration was measured by high temperature combustion on a Shimadzu TOC 5000 analyzer, as described in Sohrin and Sempéré (2005). A four-point calibration curve was constructed daily with standards prepared by diluting a stock solution of potassium hydrogen phthalate in Milli-Q water.…”
Section: Particulate and Dissolved Organic Carbon (Poc And Doc) Determimentioning
confidence: 99%